Breeding Birds at the Chittagong University Campus of Chittagong in Bangladesh - Ahsan, M Farid; Islam, M Manirul (Journal of the Asiatic Society of Bangladesh, Science, 2019)
A study on the breeding birds in the Chittagong University Campus (CUC) of Chittagong, Bangladesh was carried out, through direct field observations during January to Junee 2011. Fifty-five species of birds belonging to 27 families under 11 orders were observed to breed in the CUC. A total of 819 breeding pairs of birds were recorded, of which 25 (45.45%) species were passerines and 30 (54.55%) nonpasserines. Among the breeding birds, the Asian pied starling (Gracupica contra) was the highest in number/frequency, comprised 128 (15.63% of the total) pairs and yellow footed green pigeon (Treron phoenicopterus) was the lowest, 1 (0.12% of the total) pair. Among the 27 families, Family Corvidae comprised the highest number of breeding species (7, 12.73%); Family Sturnidae and Passeridae had 4 species each (7.27%); while 4 families included 3 (5.46%), 7 families had 2 (3.64%) and 14 families had only 1 (1.82%) breeding species each. The maximum nest building was recorded in April 276 (33.70%) and minimum in January 31 (3.78%). The highest number of nests were built in plants 370 (45.18%) and among the rest 279 (34.06%) in buildings, 116 (14.16%) in hill slopes, 46 (5.62%) in lampposts and 8 (0.98%) in the ground. The birds were recorded to use 32 species of plants under 20 families, of which 21 (65.63%) were indigenous and 11 (34.37%) were exotic species for breeding purpose only. Mango (Mangifera indica) supported the highest number of bird species for nesting about 59 (15.94%) while the second highest was coconut (Cocos nucifera) 52 (14.05%), and plant species like Bhadi (Garuga pinnata) and Pitraj (Aphanamixis polystachya) was the lowest species of only 1 (0.27%). Among the 370 nests, 295 (79.73%) were recorded in the indigenous plants and the rest 75 (20.27%) were in the exotic species. Habitat degradation and destruction, pollution in and around CUC, planting exotic species, human settlements, collection of litters and firewood, and occasional fires are hampering breeding activities of birds in the CUC. Necessary steps are to be taken to overcome the problems and protect their breeding and feeding habitats, and further study is needed to know detail of their breeding behaviour Asiat. Soc. Bangladesh, Sci. 45(1): 1-14, June 2019